KONSEP KHALIFATULLAHU FIL ARDL: DEKONSTRUKSI CORPORATE SOCIAL RESPONSIBILITY - Wulan Retnowati; Roza Mulyadi (Universitas PGRI Madiun, 2018)
The purpose of this research is to deconstruct the concept of corporate social responsibility that has failed in practice. Because there are still many tendency of company practices that only have the character of ceremonial course and aim to abort the obligation and the emergence of environmental destruction practices by companies that have implemented corporate social responsibility. This research used the concept khalifatullahufilardl, in Islam it is meansthathe human function on earth as the ruler of the universe. By deconstructing the concept of corporate social responsibility that only refers to the singgle bottom line that focus on God SWT as stakeholders, the concept khalifatullahufilardl can be applied in changing the paradigm of corporate social responsibility so that ultimately the practice of corporate social responsibility will be more aware on sustainable development and ultimately can increase corporate profits that will have an impact on increasing mutual prosperity (between companies and surrounding communities.corporate social responsibility, khalifatullahufilardl, ruler of the universe